Predicting the polarization dependence of two-mode fiber interferometers from the far-field intensity patterns - Doma, J R; Blake, J (Optics letters, 1992)
We show that the polarization dependence of the interference between differing spatial modes of an optical fiber under axial strain can be experimentally determined purely from the far-field intensity patterns of those modes.